2013
DOI: 10.4103/0974-7753.114703
|View full text |Cite
|
Sign up to set email alerts
|

Monilethrix with variable expressivity

Abstract: Monilethrix is a rare autosomal dominant hair shaft disorder with variable expressivity. It usually presents with short broken scalp hairs and follicular hyperkeratosis. Light microscopy of hair reveals a beaded appearance. Here, we report the case of a 32-year-old male who presented with sparse hair and follicular keratotic papules in the absence of any family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Severity varies substantially among cases, from a limited occipital distribution to diffuse involvement of eyebrows, eyelashes, secondary sexual hair, teeth, and nails. 4 The diagnosis of monilethrix was confirmed in this patient after pulling several scalp hairs at the root and examining on ×4 microscopy. The characteristic beaded appearance of the hair shaft was noted (Figure , B).…”
mentioning
confidence: 60%
“…Severity varies substantially among cases, from a limited occipital distribution to diffuse involvement of eyebrows, eyelashes, secondary sexual hair, teeth, and nails. 4 The diagnosis of monilethrix was confirmed in this patient after pulling several scalp hairs at the root and examining on ×4 microscopy. The characteristic beaded appearance of the hair shaft was noted (Figure , B).…”
mentioning
confidence: 60%
“…The diagnosis of monilethrix was more difficult to establish in our patient owing to the absence of any familial cases. A de novo mutation could explain why this boy was the only one in the family to be affected by this hair disease [4]. As penetrance of the disease is also variable from one subject to another, the diagnosis may have been missed in one of the two parents despite a thorough examination.…”
Section: Case Discussionmentioning
confidence: 99%
“…Monilethrix is a rare hereditary condition affecting the shaft of the hair. It was described for the very first time in 1879 by Walter Smith as “a rare nodose condition of hair.”[ 1 ] The term monilethrix was given by Radcliffe Crocker has a Latin-Greek origin; monile (necklace) and thrix (hair), describing the beaded appearance of hair. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed the mutations associated with the autosomal dominant type of monilethrix are those in exon 1 and 7 of KRT86, KRT81, and KRT83 genes, whereas the autosomal recessive type is associated with a mutation in desmoglein-4. [ 1 3 4 5 ]…”
Section: Discussionmentioning
confidence: 99%